1984
DOI: 10.1038/hdy.1984.62
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of the genetic background and ethanol on the alcohol dehydrogenase polymorphism in Drosophila melanogaster

Abstract: SUMMARYEight freshly caught Australasian mass collections ranging in Adh F frequency from 4 to 96 per cent were each divided into eight selection lines. Two selection lines from each base population were put on one of four types of mediumstandard food supplemented with 0 per cent, 3 per cent, 6 per cent or 9 per cent ethanol. After 30 generations the tolerance of 6 per cent and 9 per cent selection lines on a test dose of 9 per cent ethanol was greater than that of the 0 per cent lines on this dose. The tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 34 publications
3
21
2
1
Order By: Relevance
“…Several laboratory experiments indicate that AdhF reaches higher equilibrium frequencies in ethanol supplemented food compared with unsupplemented controls (van Delden, 1982). However, these results were generally obtained with populations which had been in laboratory culture for at least a year (Oakeshott, Gibson and Wilson, 1984). There is a similarity between the results obtained here-an increase in AdhF allele frequency for all populations where allele frequency changes-and the above.…”
Section: Fitness and Temperaturecontrasting
confidence: 29%
See 1 more Smart Citation
“…Several laboratory experiments indicate that AdhF reaches higher equilibrium frequencies in ethanol supplemented food compared with unsupplemented controls (van Delden, 1982). However, these results were generally obtained with populations which had been in laboratory culture for at least a year (Oakeshott, Gibson and Wilson, 1984). There is a similarity between the results obtained here-an increase in AdhF allele frequency for all populations where allele frequency changes-and the above.…”
Section: Fitness and Temperaturecontrasting
confidence: 29%
“…The possibility that the extremes of this temperature range are not sufficiently stressful in regard to levels of expressed genetic variation and phenotypic fitness differences is also considered. Further, following Oakeshott, Gibson and Wilson (1984) who have shown that a significant change in Adh allele frequency in response to selection on ethanol media is associated with laboratory populations and not with base populations closely related to nature, the possibility that significant results for the Adh locus are principally detected for laboratory adapted strains is considered. Finally, the contrast between (a) and (b) above permits the possibility of discussing the results in the context of domestication.…”
Section: Introductionmentioning
confidence: 99%
“…We could not detect any difference between samples collected in distilleries and farmyards in their allele frequency distribution at any of the loci investigated. Thus our results supported those surveys, where no significant differences were found in AdhF allele frequency among habitats with different alcohol concentration in the breeding substrate (eg Oakeshott et al, 1984). In two further surveys ; K Pecsenye and A Saura, unpublished), we found that ADH activities and alcohol tolerance were similar in distillery and farmyard samples both in the adult and in the larval stages.…”
Section: Discussionsupporting
confidence: 80%
“…However no other data on ethanol levels were given and it is possible that they were similar to those measured from leaking barrels of sherry at All Saints. It thus seems unlikely that levels of ethanol are implicated in the differences between the studies, although it remains possible that the mode of exposure to ethanol was important in bringing about the variation in AdhF frequencies (Oakeshott and Gibson, 1981).…”
Section: Discussionmentioning
confidence: 93%